Some motor skills and their contribution to the technical performance of the passing and dribbling skills of Al-Diwaniyah Club's junior football players - اللامي, أ.د. نوار عبدالله حسين; Al-Lami, Dr. Ghaith Abdullah Hussein; Al-Lami, Dr. Wael Abdullah Hussein (Sulaimani Journal for Humanities, 2026)
Football has evolved in many ways, including in its learning and training methods, particularly in developing and improving motor skills. The importance of this study lies in identifying the contribution of motor skills to the technical performance of dribbling and passing, and the extent of that contribution. The study aims to determine the impact of specific motor skills and their contribution to the technical performance of passing and dribbling among players of Al-Diwaniyah Football Club. The researchers hypothesize a significant contribution of motor skills to the technical performance of dribbling and passing among the research sample. They conclude that there is a strong correlation between the selected skills and motor skills in general.
Keywords: Motor skills; football